2014
DOI: 10.1158/1078-0432.ccr-14-0879
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class I Loss Is a Frequent Mechanism of Immune Escape in Papillary Thyroid Cancer That Is Reversed by Interferon and Selumetinib TreatmentIn Vitro

Abstract: Purpose To evaluate Major Histocompatibility Complex (MHC) Class I expression on papillary thyroid cancer (PTC) and analyze changes in MHC expression and associated immune activation with current and experimental treatments for thyroid cancer using in vitro PTC cell lines. Experimental Design MHC Class I expression and assessment of tumor infiltrating leukocyte populations were evaluated by immunohistochemistry. PTC cell lines were analyzed for HLA-ABC expression by flow cytometry following tyrosine kinase i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 45 publications
3
80
0
4
Order By: Relevance
“…Due to the complexity of the HLA genetic system and the difficulties in measuring the HLA-I expression in human tissue, the available information on tumor HLA-I expression does not always reflect the real pattern and the character of HLA-I alterations [15]. Additional detailed analysis is required to obtain a more accurate picture of HLA-I defects and the underlying molecular mechanisms in a given type of cancer.…”
Section: Tumor Immune Escape and Hla Class I Lossmentioning
confidence: 99%
“…Due to the complexity of the HLA genetic system and the difficulties in measuring the HLA-I expression in human tissue, the available information on tumor HLA-I expression does not always reflect the real pattern and the character of HLA-I alterations [15]. Additional detailed analysis is required to obtain a more accurate picture of HLA-I defects and the underlying molecular mechanisms in a given type of cancer.…”
Section: Tumor Immune Escape and Hla Class I Lossmentioning
confidence: 99%
“…35 In TC, type I and type II IFNs in vitro induced the expression of MHC-I molecules on human TC cell lines, thus impeding TC immunoevasion and potentiating TC susceptibility to immune destruction. 36 …”
Section: Cytokinesmentioning
confidence: 99%
“…Most of the studies have shown that MEK inhibition can increase the expression of intrinsic and IFN-γ-induced HLA/ MHC I/II in cancer cell lines, including melanoma, mesothelioma, prostate, gastric, and esophageal cancer cell lines [103][104][105]. Similarly to BRAF inhibition, treatment of mutant melanoma cell lines with MEK inhibition enhances the expression of melanoma-differentiation antigens [92] and decreases the production of IL-10, IL-6, and VEGF [91].…”
Section: Mek Inhibitionmentioning
confidence: 99%